How much influence does the Chinese state have over CEOs and their compensation? - Bryson, Alex; Forth, John; Zhou, Minghai (Emerald, 2014)
All that we know about the CEO labour market in China comes from studies of public listed companies and State-owned enterprises (SOEs). This paper is the first to examine the operation of the CEO labour market across all industrial sectors of the Chinese economy. We find that the influence of the State extends beyond SOEs into many privately-owned firms. Government is often involved in CEO appointments in domestic firms and, when this is the case, the CEO has less job autonomy and is less likely to have pay linked to firm performance. Nevertheless, we find that incentive schemes are commonplace and include contracts linking CEO pay directly to firm performance, annual bonus schemes, the posting of performance bonds, and holding company stock. The elasticity of pay with respect to company performance is one or more in two-fifths of the cases where CEOs have performance contracts, suggesting many face high-powered incentives. We also show that State-owned and domestic privately-owned firms are more likely than foreign-owned firms to use incentive contracts.